2015
DOI: 10.1590/0103-8478cr20141214
|View full text |Cite
|
Sign up to set email alerts
|

Ophthalmic parameters in adult Shih Tzu dogs

Abstract: Ocular surface diseases are often diagnosed in brachycephalic dogs. The ophthalmic parameters of the Shih Tzu dogs are evaluated in this study since this breed is among the most commonly affected by these diseases. In this study, ophthalmic parameters of this breed de 0,490±0,007mm. À flaremetria a "laser",720±0, 16,118±0,460mmHg. As médias e os erros padrão, à ultrassonografia, foram de 20,255±0,134mm para diâmetro axial horizontal; de 6,624±0,031mm, para

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 18 publications
1
11
4
Order By: Relevance
“…TBUT was not considered because of the high variability of values in the control group. Besides, the normative values of TBUT in this study were lower than those reported by Ollivier et al 39 and Kobashigawa et al, 40 probably due to characteristics of the dogs evaluated. Here, half of the dogs had a brachycephalic skull conformation, which makes the eye protruded and favors tear evaporation.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…TBUT was not considered because of the high variability of values in the control group. Besides, the normative values of TBUT in this study were lower than those reported by Ollivier et al 39 and Kobashigawa et al, 40 probably due to characteristics of the dogs evaluated. Here, half of the dogs had a brachycephalic skull conformation, which makes the eye protruded and favors tear evaporation.…”
Section: Discussioncontrasting
confidence: 84%
“…Age, sex, and skull shape were also selection criteria for inclusion of dogs into the study as they affect the values of STT1. [39][40][41] A rigorous screening of animals was T A B L E 3 Video image analysis parameters related for chromatin supraorganization of the epithelial cells and the lymphocytes from the palpebral conjunctiva of dogs with and without keratoconjunctivitis sicca (KCS)…”
Section: Discussionmentioning
confidence: 99%
“…The handheld esthesiometer possesses a thin, retractable, nylon monofilament that extends up to 6 cm in length. Since normal baseline corneal sensitivity threshold range of the normal dog varies from 1.0 to 3.5 cm (Stiles et al 2001;Blocker et al, 2007;Kobashigawa et al, 2015;Venturi et al, 2016), measurements started with a nylon monofilament length of 4 cm, which is a usual initial set point for corneal sensitivity evaluation in dogs (Venturi et al, 2016). The esthesiometer was gently advanced perpendicularly toward the center of corneal surface until a slight deflection of the monofilament was noted after contact.…”
Section: Introductionmentioning
confidence: 99%
“…Esthesiometry has been studied in different species, including humans (GOLEBIOWSY et al, 2011), cats (CHANG-LING, 1989BLOCKER & VAN DER WOERT, 2001;WIESER et al, 2013), rabbits (WIESER et al, 2013), dogs (BARRETT et al, 1991WIESER et al, 2013;KOBASHIGAWA et al, 2015), chinchillas (LIMA et al, 2010;MULLER et al, 2010), alpacas (WELIHOZKIY et al, 2011;RANKIN et al, 2012), goat, guinea pigs, cows and sheep (WIESER et al, 2013), birds (LACERDA et al, 2014), turtles (SOMMA et al, 2015) and horses (BROOKS et al, 2001;KAPS et al, 2003;WIESER et al, 2013). Previous investigations have shown no significant differences between an individual's two eyes with respect to CTT evaluations (GOLEBIOWSKY et al, 2011;WIESER et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…It can be affected by several factors, including the skull anatomy and orbit that change the positioning and insertion of the eyeball in each breed, ambient temperature and humidity and age of the individual (LACERDA et al, 2014;MONÇÃO-SILVA et al, 2016). Factors that may influence the corneal touch threshold (CTT) values have already been studied in horses (BROOKS et al, 2000;KAPS et al, 2003;WIESER et al, 2013), birds (LACERDA et al, 2014), dogs (KOBASHIGAWA et al, 2015) and cats (BLOCKER & VAN DER WOERT, 2001). However, studies that addressed the mechanism and values of corneal sensitivity in horses are scarce, and when carried out, data were reported without breed subdivision (BROOKS et al, 2001;KAPS et al, 2003;WIESER et al, 2013).…”
Section: Introductionmentioning
confidence: 99%